West African Masking Traditions and Diaspora Masquerade Carnivals : History, Memory, and Transnationalism - Njoku, Raphael Chijioke (Book collections on Project MUSE., 2020)
"A revisionist account of African masquerade carnivals in transnational context that offers readers a unique perspective on the connecting threads between African cultural trends and African American cultural artifacts"--